2018
DOI: 10.1080/10494820.2018.1548488
|View full text |Cite
|
Sign up to set email alerts
|

Designing for sustainable mobile learning – re-evaluating the concepts “formal” and “informal”

Abstract: Practitioners designing for mobile learning (mLearning) and scholars exploring the same are faced with the challenge of planning for and understanding a variety of ways and places of learning. This study focuses on one crucial distinction concerning this; that of formal and informal learning. Through the analysis of contemporary research literature, we found that informal learning is represented as more enriching than formal learning. We also identified that some representations of informal learning, such as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 49 publications
0
31
0
Order By: Relevance
“…Previous research [111,113,114,116,[118][119][120] has looked into the use of a mobile phone for learning and found that PU, PEU, attitude, social influence and facilitating conditions are the most important constructs and explanatory variables for M-learning system adoption. The current study finds that just six elements (PU, PEU, task-technology fit, PR, ATT using M-learning and BIM) are the most relevant elements in M-learning adoption.…”
Section: Discussion and Implementationmentioning
confidence: 99%
“…Previous research [111,113,114,116,[118][119][120] has looked into the use of a mobile phone for learning and found that PU, PEU, attitude, social influence and facilitating conditions are the most important constructs and explanatory variables for M-learning system adoption. The current study finds that just six elements (PU, PEU, task-technology fit, PR, ATT using M-learning and BIM) are the most relevant elements in M-learning adoption.…”
Section: Discussion and Implementationmentioning
confidence: 99%
“…The knowledge that unintentional learning has taken place (through socialisation) could be evident immediately after or several years after the learning experience. Unintentional learning is often 'unanticipated or unorganized' and usually unacknowledged by the learner (Viberg et al, 2018).…”
Section: Informal Learningmentioning
confidence: 99%
“…Furthermore, the smartwatch enabled seamless language learning, that is, learning inside and outside the classroom and connecting formal learning and everyday real-life learning experiences. When the students learned in the real world, they could situate their learning in the environment's context, thus, making learning relevant and meaningful to them (Viberg et al, 2018). It is difficult to get timely feedback or share content amongst the students in the classroom because there are too many students in the class and the teacher cannot always help everyone.…”
Section: Smartwatchmentioning
confidence: 99%